Lobar versus Sublobar Resection in the Elderly for Early Lung Cancer: A Meta-Analysis - Ng, Josiah; Masuda, Yoshio; Ng, Jun Jie; Leow, Lowell; Choong, Andrew M. T. L.; Mithiran, Harish (The Thoracic and Cardiovascular Surgeon, 2021)
Objectives We performed a systematic review and meta-analysis of outcomes of lobectomy versus sublobar resection in elderly patients (≥65) with stage 1 nonsmall cell lung carcinoma (NSCLC).Methods We searched for relevant articles using a set of inclusion and exclusion criteria. Meta-analytic techniques were applied.Results Twelve studies (n = 5834) were chosen. Our results indicate that in the elderly, lobectomy for stage 1 NSCLC confers a survival advantage over sublobar resection. Lobectomy patients had a lower risk of death within 5 years and lower odds of local cancer recurrence. Our results show that lobectomy had a better 5-year cancer-specific survival and 5-year disease-free survival that trended toward significance. The sublobar resection group showed better 30-day operative mortality that trended toward significance. Subgroup analysis of stage 1A cancer demonstrated no difference in 5-year overall survival rates. However, for stage 1B tumors 5-year overall survival favored lobectomy.Conclusion Lobectomy for stage 1 NSCLC in elderly patients is superior to sublobar resection in terms of survival and cancer recurrence and should be afforded where possible. For stage 1A tumors, sublobar resection is noninferior and may be considered. Further randomized controlled trials in this topic is required.
Keywords: lobectomy; segmentectomy; lung cancer; elderly